2011
DOI: 10.1001/archophthalmol.2010.337
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Serous Retinal Detachment in Patients With Uveitic Macular Edema

Abstract: To assess the clinical characteristics and effect on visual acuity (VA) of a subfoveal serous retinal detachment (SRD) associated with macular edema (ME) in patients with uveitis.Methods: Clinical and optical coherence tomograph characteristics were retrospectively assessed in 37 patients with uveitic ME with a subfoveal SRD (case individuals) and 61 patients with uveitic ME without a subfoveal SRD (control individuals), matched for uveitis location, sex, and age. Scans of the case and control individuals took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
1
18
3
1
Order By: Relevance
“…But as soon as 1 day after IVTA administration, BCVA gain was significantly higher, and eyes with initial SRD showed less CME relapses than eyes without SRD. A retrospective study 12 of uvCME has already shown that eyes with SRD have a lower visual acuity and a greater CRT at baseline than non-SRD eyes, but there was no difference between these two groups after therapy. Another study with a mean follow-up of 5.2 months found a visual acuity improvement in 70% and a stabilization in 30% of the eyes showing SRD at baseline, but only 48.5% showed visual acuity improvement and 61.5% visual acuity showed stabilization without baseline SRD.…”
Section: Subretinal Detachment and Epiretinal Membrane As Predictive mentioning
confidence: 96%
See 2 more Smart Citations
“…But as soon as 1 day after IVTA administration, BCVA gain was significantly higher, and eyes with initial SRD showed less CME relapses than eyes without SRD. A retrospective study 12 of uvCME has already shown that eyes with SRD have a lower visual acuity and a greater CRT at baseline than non-SRD eyes, but there was no difference between these two groups after therapy. Another study with a mean follow-up of 5.2 months found a visual acuity improvement in 70% and a stabilization in 30% of the eyes showing SRD at baseline, but only 48.5% showed visual acuity improvement and 61.5% visual acuity showed stabilization without baseline SRD.…”
Section: Subretinal Detachment and Epiretinal Membrane As Predictive mentioning
confidence: 96%
“…When connections between the retinal tissues are damaged (e.g., because of ischemic conditions), fluid causes CME but may not be able to cause traction force and therefore SRD. Previous work 12,47 has associated the presence of SRD in CME with shorter disease duration. Conversely, SRD was not associated with the CME disease duration in our study population, although disease duration as well as age were almost significant factors in the models evaluated.…”
Section: Subretinal Detachment and Epiretinal Membrane As Predictive mentioning
confidence: 99%
See 1 more Smart Citation
“…Although DME was found to be associated with poor visual recovery after treatment [50], some studies point to a negative visual outcome in patients with uveitic CME [45,48,51,52]. The presence of serous retinal detachment in eyes with uveitic macular edema has been shown not to worsen the visual prognosis [50,53]. Lehpamer et al [54], using SD OCT, analyzed the effect of presence of subretinal fluid in patients with uveitic macular edema on visual acuity and response to therapy.…”
Section: Use Of Optical Coherence Tomography Technology In Uveitis Prmentioning
confidence: 99%
“…Glucocorticoids efficiently reduce macular edema of many origins, even when associated with subretinal fluid (Noma et al, 2012;Ossewaarde-van Norel et al, 2011), but glucocorticoids can aggravate subretinal fluid accumulation in CSCR patients. Even exposure to low-dose non-ocular corticosteroids has been associated with the occurrence of CSCR (Bouzas et al, 2002;Thinda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%